Formulasi dan Uji Mutu Fisik Sediaan Sabun Padat Herbal Ekstrak Daun Ubi Jalar Ungu (Ipomea batatas L) dengan Penambahan Madu - Nandani, Risha; Arif, M. Rizky; Purwati, Elly; Safitri, Cikra Ikhda Nur Hamidah (Universitas Muhammadiyah Surakarta, 2021)
Purple sweet potato (Ipomea batatas L) is one of the most familiar tuber plants found in Indonesia. In purple sweet potato leaves, there are flavonoid compounds, polyphenols and saponins that have antibacterial activity. Honey is beneficial for health, including as an antibacterial because it contains hydrogen peroxide, flavonoid compounds, essential oils and various other organic compounds. Soap is one of the cosmetic preparations which is well known as a body cleanser which is shown for external use on the human body. This study aims to obtain a solid herbal soap formulation of purple sweet potato leaf extract (Ipomea batatas L) with the addition of physically stable honey. The design of this research is experimental research. Purple sweet potato leaf extract was obtained from the maceration process using 70% ethanol solvent and formulated into soap preparations with variations in the formulation concentration of 1% and 3%. In making soap, the Cold Process method is applied. Evaluation of preparations carried out includes pH test, foam power test, organoleptic test and homogeneity test. The research results were processed using descriptive analysis. The evaluation results of soap preparations showed that the two formulations were stable to meet the standard ph test, foam power test, organoleptic test and homogeneity test. The conclusion is that the soap preparation that has the best physical stability is formula 1 with 1% concentration of purple sweet potato leaf extract.